Neuroprotection of ischemic preconditioning is mediated by thioredoxin 2 in the hippocampal CA1 region following a subsequent transient cerebral ischemia. (27th June 2016) - Lee, Jae‐Chul; Park, Joon Ha; Kim, In Hye; Cho, Geum‐Sil; Ahn, Ji Hyeon; Tae, Hyun‐Jin; Choi, Soo Young; Cho, Jun Hwi; Kim, Dae Won; Kwon, Young‐Guen; Kang, Il Jun; Won, Moo‐Ho; et al.
Abstract: Preconditioning by brief ischemic episode induces tolerance to a subsequent lethal ischemic insult, and it has been suggested that reactive oxygen species are involved in this phenomenon. Thioredoxin 2 (Trx2), a small protein with redox‐regulating function, shows cytoprotective roles against oxidative stress. Here, we had focused on the role of Trx2 in ischemic preconditioning (IPC)‐mediated neuroprotection against oxidative stress followed by a subsequent lethal transient cerebral ischemia. Animals used in this study were randomly assigned to six groups; sham‐operated group, ischemia‐operated group, IPC plus (+) sham‐operated group, IPC + ischemia‐operated group, IPC + auranofin (a TrxR2 inhibitor) + sham‐operated group and IPC + auranofin + ischemia‐operated group. IPC was subjected to a 2 minutes of sublethal transient ischemia 1 day prior to a 5 minutes of lethal transient ischemia. A significant loss of neurons was found in the stratum pyramidale (SP) of the hippocampal CA1 region (CA1) in the ischemia‐operated‐group 5 days after ischemia‐reperfusion; in the IPC + ischemia‐operated‐group, pyramidal neurons in the SP were well protected. In the IPC + ischemia‐operated‐group, Trx2 and TrxR2 immunoreactivities in the SP and its protein level in the CA1 were not significantly changed compared with those in the sham‐operated‐group after ischemia‐reperfusion. In addition, superoxide dismutase 2 (SOD2) expression, superoxide anion radical ( O 2 − ) production, denatured cytochrome c expression and TUNEL‐positive cells in the IPC + ischemia‐operated‐group were similar to those in the sham‐operated‐group. Conversely, the treatment of auranofin to the IPC + ischemia‐operated‐group significantly increased cell damage/death and abolished the IPC‐induced effect on Trx2 and TrxR2 expressions. Furthermore, the inhibition of Trx2R nearly cancelled the beneficial effects of IPC on SOD2 expression, O 2 − production, denatured cytochrome c expression and TUNEL‐positive cells. In brief, this study shows that IPC conferred neuroprotection against ischemic injury by maintaining Trx2 and suggests that the maintenance or enhancement of Trx2 expression by IPC may be a legitimate strategy for therapeutic intervention of cerebral ischemia.